Maximizing botulinum toxin injections for cosmetic and therapeutic applications with a single use, disposable, exact dose injection assist device - Kwolek MS; Block JE (Dove Medical Press, 2019)
Marilyn S Kwolek,1 Jon E Block2 1Private Practice, Danville, CA 94526, USA; 2Independent Clinical Consultant, San Francisco, CA 94115, USA Background: Although freehand injection of botulinum toxin remains the status quo, it is an inaccurate technique for delivering precise amounts of neurotoxin at multiple injection sites with expediency. We developed an inexpensive, ergonomic, single-use, disposable exostructure device that rapidly converts a standard syringe into a highly accurate injection instrument. Materials and methods: Based on the results of two independent injectors, we determined the comparative delivery dose accuracy, precision, and amount of product waste associated with a standard syringe using the freehand injection technique vs a prototype injection assist device. Fifteen experienced injectors were also surveyed regarding their satisfaction using the device in a controlled research setting. Results: The average percentage difference from the expected dose value was <1% (0.00024 mL) for 1-unit doses (ie, 0.025 mL) with the injection assist device. In contrast, accuracy values with the freehand method were more than 10 times worse (ie, >10% or 0.0025 mL). Accuracy estimates were also superior with the device over freehand for 2- and 4-unit doses. Precision estimates favored the device for all comparisons and all dosing regimens. The magnitude of variability around the average difference ranged from 2.2 to 5.4 times worse for the freehand method compared to the device. The overall percentage of product waste was substantial with the freehand method (>10%) compared to the device (4.3%) (P=0.04) for 1-unit injections. The percentage of injections showing measurable product waste was also significantly lower with the device (78% vs 25%, P=0.01). Fourteen of 15 (93%) injectors surveyed would use the device in daily practice if it were included complimentary with the neurotoxin. Conclusion: The injection assist device offered superior accuracy and precision compared to the freehand method across the entire injection regimen. The ancillary finding of a significant reduction in product waste with the device was particularly notable. Keywords: neurotoxin, injection, syringe, accuracy